METHODOLOGY OF TEACHING ENGLISH IN CONTEMPORARY CLASSROOMS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Teaching English today requires more than the presentation of grammar rules and vocabulary lists. In multilingual and mixed-ability classrooms, effective methodology must combine clear language input, meaningful interaction, purposeful practice, and sensitive assessment. This article discusses the main principles of modern English language teaching with particular attention to communicative language teaching, task-based learning, lexical development, scaffolding, and formative assessment. It argues that successful instruction depends not on one fixed method, but on the teacher’s ability to select and adapt techniques in response to learners’ needs, goals, and proficiency levels. The article also highlights the role of motivation, feedback, classroom atmosphere, and reflective practice in sustaining progress. The discussion concludes that an effective methodology for teaching English should be flexible, student-centered, and grounded in both theory and classroom reality.